21=9x-33

Simple and best practice solution for 21=9x-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21=9x-33 equation:


Simplifying
21 = 9x + -33

Reorder the terms:
21 = -33 + 9x

Solving
21 = -33 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
21 + -9x = -33 + 9x + -9x

Combine like terms: 9x + -9x = 0
21 + -9x = -33 + 0
21 + -9x = -33

Add '-21' to each side of the equation.
21 + -21 + -9x = -33 + -21

Combine like terms: 21 + -21 = 0
0 + -9x = -33 + -21
-9x = -33 + -21

Combine like terms: -33 + -21 = -54
-9x = -54

Divide each side by '-9'.
x = 6

Simplifying
x = 6

See similar equations:

| t(-8t^2+16)=0 | | 12x-44-15x=7+4x | | 66x+11=22 | | 75=-39-6x | | y=x^5-4x^3+5x+1 | | 2x(x+3)=2x(2x)+15 | | 350=0.018417l | | 5x+82=-83 | | 8x^3-x-7=0 | | 3(h+2)=-(-3h+8)+6(5-h)-4 | | 22-14x=18x+90+112+4x | | 4x+23=32 | | t-5fort=7 | | -16x-37=-14x+55 | | -45+z=-47 | | (-6m^4n^2)(5mn^7)= | | 5+9x=-100 | | 40+x+5x=180 | | -2(3x-5)+8=-6x+18 | | 5+9x=100 | | 65.66*6.28= | | 3y(2x-5y)= | | .9(7x+6)=2.5-(x-3) | | 2c+5-84=3c+6 | | -16x-32=-14x+55 | | 14c+5-32=3c+6 | | 9x-4-7x-10=-8x-11+17x-3 | | Y=.20x+160 | | 14c+35-4=3c+6 | | 0.0m=20.0m+a(12s) | | 25x^2+18=98 | | (5d^2-2g^5)(3g^3-h+4d^2)=0 |

Equations solver categories